Chemical structure and anticoagulant activity of highly pyruvylated sulfated galactans from tropical green seaweeds of the order Bryopsidales - Arata, Paula Ximena (2015)
Sulfated and pyruvylated galactans were isolated from three tropical species of the Bryopsidales, Penicillus capitatus, Udotea flabellum, and Halimeda opuntia. They represent the only important sulfated polysaccharides present in the cell walls of these highly calcified seaweeds of the suborder Halimedineae. Their structural features were studied by chemical analyses and NMR spectroscopy. Their backbone comprises 3-, 6-, and 3,6-linkages, constituted by major amounts of 3-linked 4,6-O-(1′-carboxy)ethylidene-d-galactopyranose units in part sulfated on C-2. Sulfation on C-2 was not found in galactans from other seaweeds of this order. In addition, a complex sulfation pattern, comprising also 4-, 6-, and 4,6-disulfated galactose units was found. A fraction from P. capitatus, F1, showed a moderate anticoagulant activity, evaluated by general coagulation tests and also kinetics of fibrin formation was assayed. Besides, preliminary results suggest that one of the possible mechanisms involved is direct thrombin inhibition.